Efficacy of Antidepressants in Depression in Breast Cancer: A Systematic Review and Meta-analysis - Vinuta C. Chikkamath; Lingaraj Kariyannavar; Ranganath Rattehalli; B. Srinivas Pai (Journal of Psychiatry Spectrum)
Background: Breast cancer is the most common malignancy in women worldwide. Depression is a common psychological issue among these patients as they experience significant stress, and it impacts their quality of life. In this regard, the efficacy of antidepressants in depression for breast cancer is not studied. Objective: The objective of the study was to study the efficacy of antidepressants in the management of depression in breast cancer. Methods: Our databases included PubMed, MEDLINE, PsycINFO, Cochrane, Scopus, and Gray literature published in English. Studies included were randomized, placebo-controlled, double-blind trials of antidepressants for women diagnosed with breast cancer and depression. Studies were excluded if they were nonrandomized trials, had an active comparator, or if the antidepressant drug was not primarily used for depression. The severity of depressive symptoms was measured using standardized rating scales for depression. The risk of bias was assessed using the Cochrane risk of bias 2 tool. Covidence and Microsoft Excel were used for data extraction and RevMan 5.4.1 for efficacy outcome estimates, heterogeneity, and sensitivity analysis. Results: Of a total of 155 studies, 13 studies (9 parallel design and 4 crossover) met the inclusion criteria for systematic review and seven for meta-analysis involving 595 participants. The risk of bias assessment showed that five studies had low risk, four studies had some concerns, and four studies had high risk of bias. The antidepressants noted to have a favorable outcome were fluoxetine, paroxetine, mianserin, and mirtazapine. The pooled analysis (standardized mean difference [SMD] −0.28 [confidence interval = −0.56, 0.01] z = 1.87 [P = 0.06]) and subgroup analysis (selective serotonin reuptake inhibitor) did not favor antidepressants (SMD = −0.23 [−0.52, 0.07], z = 1.51, [P = 0.13]). Sensitivity analysis did not show a significant difference in outcome measures between antidepressants and placebo. Considerable heterogeneity, with a value of 69%, was found to be statistically significant (P = 0.003). Conclusion: We conclude that based on the available research, there was no evidence that antidepressants were superior to placebo in the management of depression in breast cancer. The possible reasons for heterogeneity are variations in the duration of study periods and antidepressant administration, different stages of breast cancer, and different scales used for assessing depression in RCTs.